Inquiring About The Memetic Relationships People Have with Societal Collapse - Cardinal, Monique (Transactions on Engineering and Computing Sciences, 2024)
This paper explores how information processing affects behavior and factors of societal collapse. An approach to further explore peoples’ behaviors concerning collapse is explained. Metamemetics is an approach to understanding the way we think proposed by Diego Fontanive. Factors of collapse and how we relate to it are explained in different fields. Examples in the paper use the Internet as a place to study perception of processing information. A survey was made and given for observations about user behavior and expectations. Another example survey was given out to critically observe user behavior and expectations across different websites, tracing factors of the cognitive aspect of societal collapses, such as a decline in attention span. Exploring the application of this approach is recommended when studying reality and how we relate to it, and inquiries about systems and potential societal collapse.